MEASURING THE IMPACT OF THE MONETARY MASS ON FDI FLOWS IN ALGERIA DURING THE PERIOD (1990-2020 ) USING THE ERROR CORRECTION MODEL (VECM) - Yassine , Mimouni; Mouna, Bessouyah (The journal of contemporary issues in business and government, 2024)
This study aims to measure the impact of foreign direct investment on the money supply in Algeria during the period1990-2020 through the use of the error correction model (VECM),with the aim of testing the long-term causal relationship between promising foreign investment and the money supply , and the joint integration test. After testing the stability of time series, it was found that the study variables are stable in the first degree. The results of the estimates showed that there is no causal relationship between the two variables in both directions in the short term. After testing the significance of the parameters, it was found that the error correction coefficient (CointEq) is negative and moral. This explains the existence of a long-term equilibrium relationship between the study variables with a positive impact between all money supply and changes in foreign direct investment.